COMPARISON OF THE INDONESIAN AND JAPANESE EDUCATION SYSTEMS - Ukrimah, Siti; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the comparison between the education systems of Indonesia and Japan, focusing on aspects such as curriculum structure, teacher quality, teaching methods, evaluation systems, technology integration, school culture, and government policies. The research uses a qualitative approach with a comparative study method through literature analysis from various sources such as scientific journals, government policy documents, and international organization reports for the period 2020-2024. The theories used include George Bereday's Theory of Comparative Education, Bronfenbrenner's Theory of Educational Ecology, and Michael Lipsky's Theory of Policy Implementation as the analytical framework. The results of the study show fundamental differences between the two education systems, where Japan has a more structured, consistent, and coherent system with highly selective teacher recruitment, proven effective Lesson Study and Problem-Solving-based learning methods, and a strong school culture that instills values of discipline and responsibility. Meanwhile, Indonesia's Merdeka Curriculum offers greater flexibility and autonomy, but faces challenges such as disparities in quality between regions, gaps in teacher competence, and inconsistencies in policy implementation. Japanese students consistently outperform Indonesian students in international tests such as PISA, reflecting the effectiveness of their education system. However, the Japanese system also has weaknesses in the form of extremely high academic pressure due to intense entrance exam competition. This study recommends that Indonesia can learn from Japan's best practices by improving teacher recruitment selectivity, developing a culture of professional collaboration, strengthening integrated character education, and equalizing the quality of education, while still considering Indonesia's unique social, cultural, and geographical context. Smart and gradual adaptation is more important than the direct application of the Japanese system, which may not be suitable for local conditions in Indonesia. Educational transformation requires a long-term commitment from all stakeholders and should not be influenced solely by political dynamics.